The biotic influence of biological insecticide ( Agerin) and plant growth regulator ( Match ) on the first larvae instar of spiny boll worm Earias insulana(Boisd.) (Lepidoptera:Phalaenidae) - AL-Rubaie, A.R.L.; AL-Zubadi, A.N.O.; AL- Herishawi, S. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
First  instar  larvae    of  spiny  cottcn  boll  wonn   Earias insulana(Bosid.)    were    Fed     on    different    concentrations    of    biological insecticides (Agerin) and growth  regulators (Match) for ( 5, 3 and one days) .The results showed  that Agerin at 1.5 giL caused   99.9 , 99.9. and  96.9  %  accumulative killing  percentages  while    0.5  g/L  of  this biological  insecticidt::s resulted  in  92.96 , 58.9 and 33.3% in the three periods  of  feeding    above    respectively  . On  the other  hand  growth inhibitor  (Match)  gave   99.9, 99.9 and 99.9 %accumulative killing percentage  when it was used at 1.5  ml I L ; whereas  the  percentageswere 99.9 , 66.6 and 46.6 % when it was used 0.25 ml JL. in the sameperiods  respectively   . Results  implied  also  that accwnulative killingpercentages were  increased  with  the dose  and  the nutritive  periods . Most of the larvae died when they where fed by (match) for 5 days by using  high  concentrations of  both  insecticides,  it also  observed   that these larvae did not complete  their growth stages , yet when  they were fed for 3 or one  day by using  low concentrations, they were  able  to complete   there  life  cycle  accompanied  with  delay  of  larvae  stage period  and  abnormal  behavior of  the  larvae  in  their  color,   slow movement  and less appetite. The growth regulator (Match) however, was  more  effective   in  mortality  percentage  for  the  larvae  stage  as compared  with biological  insecticide (Agerin).